A social media adoption framework as pedagogical instruments in higher education classrooms. (January 2021) - Hamadi, Mostafa; El-Den, Jamal; Narumon Sriratanaviriyakul, Cherry; Azam, Sami
Social Media (SM)'s use as pedagogical tools in Higher Education (HE) institutions is gaining robust momentum among researchers from different disciplines. While most universities implemented Learning Management Systems (Blackboard Learn, Moodle, etc.) as essential instruments in their teaching and learning(T&L) methods, the adoption of SM platforms such as Facebook, YouTube, etc., as in-class educational and communication tools is still in its infancy. Despite the numerous available studies on SM's adoption as T&L instruments in HE, little has been made to develop a standard framework for SM's integration as effective educational tool in classroom environments. This paper followed a thematic review of 19 relevant studies to analyse and identify common practices and findings on SM's inclusion as T&L tools in HE. Subsequently, the findings formed the basis in developing a conceptual framework for SM's integration as pedagogical tools in HE classrooms. This framework introduces SM's adoption process as a formal educational tool, the development of SM implementation processes, and assists in understanding the influence of SM on education environments. The research outlines major findings in current literature, thereby, providing valuable insights on SM's use in education, besides forming the basis for future quantitative and qualitative researches in this area of study.